2020
DOI: 10.1177/1558925020985959
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic wave shielding and mechanical properties of vapor-grown carbon nanofiber/polyvinylidene fluoride composite fibers

Abstract: The demand for multifunctional requirements in aerospace, military, automobile, sports, and energy applications has encouraged the investigation of new conductive composite fibers. This study focuses on the development of Vapor-grown carbon nanofibers (VGCNFs) filled Polyvinylidene Fluoride (PVDF) composite fibers. Polyvinylidene fluoride (PVDF) reinforced with (1, 3, 5, and 8 wt.%) carbon nanofibers were produced as a masterbatch. The production of PVDF and PVDF/CNF composite fibers have been done successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Hybrid fiber composites can have various applications, such as in healthcare, defense, fashion and entertainment, sportswear, purpose clothing, and transportation, as well as integration with advanced technology [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. To date, research on cutting-edge hybrid fiber materials is being conducted [ 4 , 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid fiber composites can have various applications, such as in healthcare, defense, fashion and entertainment, sportswear, purpose clothing, and transportation, as well as integration with advanced technology [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. To date, research on cutting-edge hybrid fiber materials is being conducted [ 4 , 5 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the mechanical properties were reduced and increased at the weight fractions of 0.5% and 0.9%, respectively. Yuksek 11 studied the mechanical properties of polyvinylidene fluoride (PVDF) filled with vapor-grown carbon nanofibers (VGCNFs) reinforced with conductive plain-weave fabrics. An increase in VGCNFs content up to 3% led to an increase in the tensile strength and strain of composites, followed by a decrease.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In particular, studies have reported various nanocarbon materials as functional llers, such as carbon black (CB), 9,10 carbon nanotubes (CNTs), [11][12][13] graphene nanoplates (GNPs) [14][15][16][17] and vapour-grown carbon bres (VGCFs). 18 Due to their lamellar shape and high-aspect-ratio structure, GNPs are suitable for EMI shielding materials in applications requiring good conductivity. 19 Therefore, many studies have reported composite materials with GNPs as conductive llers.…”
Section: Introductionmentioning
confidence: 99%
“…6–8 In particular, studies have reported various nanocarbon materials as functional fillers, such as carbon black (CB), 9,10 carbon nanotubes (CNTs), 11–13 graphene nanoplates (GNPs) 14–17 and vapour-grown carbon fibres (VGCFs). 18…”
Section: Introductionmentioning
confidence: 99%